2009
DOI: 10.1016/j.pec.2008.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Can dimensions of national culture predict cross-national differences in medical communication?

Abstract: The understanding of these cross-national differences is a precondition for the prevention of intercultural miscommunication. Improved understanding may occur at microlevel in the medical encounter, as well as on macrolevel in pursuing more effective cooperation and integration of European health care policies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
95
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(104 citation statements)
references
References 21 publications
8
95
1
Order By: Relevance
“…Countries with low power distance show a preference for a more patient-centred approach whereby the patient is involved in their treatment and diagnosis, and is able to ask questions. However, Meeuwesen et al (2009) found that, contrary to their expectations, the more feminine a country was, the more instrumental communication there was between GPs and patients, with a lot of questionasking by both doctor and patient, and much biomedical information exchange; in masculine countries, there was more affective than instrumental communication. In individualist countries, there was high exchange of psychosocial information.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…Countries with low power distance show a preference for a more patient-centred approach whereby the patient is involved in their treatment and diagnosis, and is able to ask questions. However, Meeuwesen et al (2009) found that, contrary to their expectations, the more feminine a country was, the more instrumental communication there was between GPs and patients, with a lot of questionasking by both doctor and patient, and much biomedical information exchange; in masculine countries, there was more affective than instrumental communication. In individualist countries, there was high exchange of psychosocial information.…”
Section: Discussioncontrasting
confidence: 60%
“…Some studies have been carried out in the healthcare context using one or more of the dimensions as a framework. These include studies in relation to cross-national differences in antibiotic use (Deschepper et al 2008), blood transfusion practices (de Kort et al 2010), medical communication between general practitioners (GPs) and patients (Meeuwesen et al 2009), and attitudes of medical practitioners towards medical professionalism (Chandratilake et al 2012).…”
Section: Practice Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…This country-specific effect might be rooted in a general difference in medical culture between the two countries, as physicians in The Netherlands tend more toward the formalization of practices. 40,41 Also, the political and societal debate concerning euthanasia and other end-of-life decisions has a longer history in The Netherlands than in Belgium, and the Dutch Medical Treatment Contracts Act, 10 in which the importance of the patient's written authority for medical treatments has to be made explicit to them, has been in place several years longer than the Belgian Law on Patient Rights. 9 As a result, advance directive forms in The Netherlands (widely promoted by the Dutch Association for Voluntary Euthanasia) are more widespread compared with Belgium, which also may be part of the explanation.…”
Section: Discussionmentioning
confidence: 99%
“…[37] Indeed, differences in national health policy play a role in the priority and implementation of patient education. [38] However, within-cultural differences also exist as the organizational climate perceptions (i.e.…”
Section: Introductionmentioning
confidence: 99%